Groundwater resources of Uzbekistan: an environmental and operational overview - Rakhmatullaev, Shavkat A.; Huneau, F.; Kazbekov, Jusipbek S.; Celle-Jeanton, H.; Motelica-Heino, M.; Le Coustumer, Philippe; Jumanov, J. (Walter de Gruyter GmbH, 2012)
As a result of the massive irrigation development during the Soviet Union era and intensive chemization of agriculture, the surface runoff quality has been degraded in this arid and endorheic region. Moreover hydraulically related groundwater has also been affected. Excessive irrigation has lead to land salinization, which now threatens the soil quality of significant areas where crop yields would be at risk in the future. Since the collapse of the Soviet Union, institutional changes have been undertaken for the management of natural resources and water infrastructure. At present, underdeveloped and inadequate systems have been practiced with respect to groundwater use and management. This paper analyzes the present extent of groundwater resources with consideration to their reserves, quality evolution, and to technical, institutional and transboundary management practices in Uzbekistan.